The awareness and utilization of maternity benefit schemes among women receiving postnatal services in a tertiary care centre - K., Manjula; K. S., Ravish; T. S., Ranganath (International Journal Of Community Medicine And Public Health, 2017)
Background: Successive governments have introduced various schemes to improve the institutional deliveries & reduce the maternal mortality ratio. Non-utilization or underutilization of the schemes is either due to lack of awareness or poor accessibility. Hence this present study is undertaken to assess awareness & utilization of the Government Maternity Benefit Schemes (MBS) in a tertiary care center among postnatal women which caters maternal and child health services to a varied and large group of women. Methods: A cross sectional study was conducted among women in the postnatal wards of Vanivilas hospital, a tertiary care center in Bengaluru regarding awareness and utilization of the government maternity benefit schemes. Results: Awareness of the schemes varied from 86% to 32%, for the four schemes, while utilization was found maximum for Janani Shishu Suraksha Karayakram (JSSK) 98%, followed by Madilu Yojana 60%, Janani Surakshayojana 56%, and least was Prasooti Araike with 15%. Conclusions: Awareness is better compared to previous studies yet utilization of some schemes remains low. Conditional cash transfers have become popular in India as evident by the rise in the number of institutional deliveries.